Caristi’s Fixed Point Theorem and Subrahmanyam’s Fixed Point Theorem in ν-Generalized Metric Spaces - Badriah Alamri; Tomonari Suzuki; Liaqat Ali Khan (Journal of Function Spaces)
We discuss the completeness of ν-generalized metric spaces in the sense of Branciari. We also prove generalizations of Subrahmanyam’s and Caristi’s fixed point theorem.